Kreatywność leksykalna a etyka słowa (na przykładzie komentarzy internetowych) - Kaproń-Charzyńska, Iwona; Wiśniewski, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The paper addresses the issue of lexical creativity in the context of language communication. The subject of the discussion is modern Polish vocabulary as an element of the linguistic concretization of the media images of the world effected in Internet comments. The authors are of the opinion that, as a crucial component of the Internet discourse, lexical creativity is connected with the issue of esthetics on the one hand and the problem of morality set in the framework of the true or false image of the world presented in the media on the other. The analysis of the linguistic material derived from Internet comments on articles about politics is meant to demonstrate connections between the creative use of lexis and evaluation. The authors provide a typology of expressions displaying features of lexical creativity and describe the types of motivation behind the linguistic activity of the senders. They demonstrate how the senders use the language mechanisms that allow them to create ambiguous expressions in which the poetic and ludic functions are subjected to a negative evaluation of real events and do not affect the reception of these expressions in terms of esthetics.